Le style cinématographique d'Alain Resnais, de Hiroshima mon amour (1959) aux Herbes folles (2009) = The film style of Alain Resnais, Hiroshima mon amour (1959) to Wild grass (2009) - Walker-Morrison, Deborah (Edwin Mellen Press, 2012)
This text tracks changes in French critical theory on the topic of subjectivity and analyzes how these theoretical developments apply to the films of Alain Resnais. It claims that the purpose of Resnais' oeuvre is the transition from modernist tendencies towards absolute mastery and control, to postmodern, deconstructionist movements towards a de-centered storyline and subject.